Assessment of Bacterial Community Structure, Associated Functional Role, and Water Health in Full-Scale Municipal Wastewater Treatment Plants - Inderjeet Tyagi; Kaomud Tyagi; Faheem Ahamad; Rakesh Bhutiani; Vikas Kumar (Toxics)
The present study collected wastewater samples from fourteen (14) full-scale wastewater treatment plants (WWTPs) at different treatment stages, namely, primary, secondary, and tertiary, to understand the impact of WWTP processes on the bacterial community structure, their role, and their correlation with environmental variables (water quality parameters). The findings showed that the bacterial communities in the primary, secondary, and tertiary treatment stages are more or less similar. They are made up of 42 phyla, 84 classes, 154 orders, 212 families, and 268 genera. Proteobacteria, Bacteroidetes, Cloacimonetes, Firmicutes, Euryarchaeota, Verrucomicrobia, Cyanobacteria, Desulfomicrobium, Thauera, Zavarzinia, and Nitrospirae, among others, dominated the bacterial community structure in all treatment stages. The biochemical oxygen demand was 7–12 times, chemical oxygen demand (COD) was 6 times, and total suspended solids (TSS) was 3.5 times higher in the wastewater than what the Central Pollution Control Board (CPCB) in New Delhi, India, allows as standard discharge. The correlation analysis using the Pearson r matrix and canonical correspondence analysis (CCA) also confirmed the fact that these water quality parameters (especially BOD and COD) play a pivotal role in deciphering the community structure in WWTPs.